2023
DOI: 10.3389/fpubh.2023.1147026
|View full text |Cite
|
Sign up to set email alerts
|

Association between adverse oral conditions and cognitive impairment: A literature review

Abstract: Oral environment deterioration results from a lack of self-cleaning ability in patients with cognitive dysfunction but is also a risk factor for cognitive dysfunction. Adverse oral conditions can be alleviated and improved through a self-management and medical examination. In this review, the epidemiological evidence of previous studies is integrated to highlight the relationship between periodontitis, tooth loss, oral flora, oral dysfunction and cognitive dysfunction, emphasizing the importance of oral health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
(69 reference statements)
1
0
0
Order By: Relevance
“…These conflicting results imply that living alone may not be a reliable indicator of loneliness. Furthermore, the study revealed a correlation between cognitive impairment and self-reported poor oral health, which has been consistent with previous research [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…These conflicting results imply that living alone may not be a reliable indicator of loneliness. Furthermore, the study revealed a correlation between cognitive impairment and self-reported poor oral health, which has been consistent with previous research [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 92%